2020
DOI: 10.1155/2020/9742754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Hospitalized Patients with Drug-Induced Acute Kidney Injury and Associated Risk Factors: A Case-Control Study

Abstract: Background. Drug-induced acute kidney injury (D-AKI) is increasingly common and can extend the hospital length of stay and increase mortality. This study is aimed at analyzing the clinical characteristics of hospitalized patients with D-AKI and the associated risk factors in a multidrug environment. Methods. A retrospective study among hospitalized patients was conducted in July 2019 based on the Adverse Drug Events Active Surveillance and Assessment System-2 developed by the authors. Four controls were matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…The pathological mechanism by which NSAIDs precipitate hemodynamically mediated kidney injury is the inhibition of renal prostaglandins, causing renal vasoconstriction to occur preferentially in the afferent arteries ( Khan et al, 2017 ; Guan et al, 2019 ). In addition, use of diuretics was found to be a risk factor for D-AKI in many studies ( Kane-Gill and Goldstein, 2015 ; Caspi et al, 2017 ; Yu et al, 2020 ). The mechanism is to stimulate the sympathetic nervous system and the renin-angiotensin system (RAS), which leads to hemodynamic changes and eventually renal perfusion deficit leading to AKI ( Wang C. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathological mechanism by which NSAIDs precipitate hemodynamically mediated kidney injury is the inhibition of renal prostaglandins, causing renal vasoconstriction to occur preferentially in the afferent arteries ( Khan et al, 2017 ; Guan et al, 2019 ). In addition, use of diuretics was found to be a risk factor for D-AKI in many studies ( Kane-Gill and Goldstein, 2015 ; Caspi et al, 2017 ; Yu et al, 2020 ). The mechanism is to stimulate the sympathetic nervous system and the renin-angiotensin system (RAS), which leads to hemodynamic changes and eventually renal perfusion deficit leading to AKI ( Wang C. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ADE-ASAS-2 was based on trigger technology and text recognition technology, which can be connected to the HIS to extract patient information. Detailed descriptions of the ADE-ASAS-2 and its applications have been described in our previous study ( Chen et al, 2020 ; Yu et al, 2020 ). Once the monitoring indicators trigger the inclusion criteria, the system could preliminarily determine whether a patient has developed AKI and indicate early warning signals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al conducted a retrospective study, which included 21,131 patients. The authors reported an association between NSAIDs and drug‐induced AKI—OR = 2.39 (95% CI: 1.25–4.58) 26 . Furthermore, Pham et al found that antenatal indomethacin increases the risk of AKI in neonates.…”
Section: Acute Kidney Injury and Nsaidsmentioning
confidence: 99%
“…The causality score ranges from −9 to 14 points. The scores are divided into highly probable (≥9), probable (6)(7)(8), possible (3)(4)(5), unlikely (1)(2) or excluded (<0). 4 Patients with RUCAM ≥ 6 points were directly included in the case group, and patients with RUCAM scores of 3-5 points were evaluated back-to-back again by the investigator based on the patient's medical history and disease progression.…”
mentioning
confidence: 99%